Designing a Website Based Aceh Translation Application Using Rule-Based - Fadhliati, Fadhliati (International Journal Education and Computer Studies (IJECS), 2021)
Language is a means of communication between community members in the form of sound symbols produced by human speech tools, language is also a means of self-expression as well as a tool to show self-identity. With the very rapid development of technology, especially in the field of information technology, the problems previously described can be overcome by building a web-based text to Aceh language translator system. Research on the translation system uses three main approaches, namely a rule-based, statistical and example-based approach. The method used consists of 2 (two), namely the system development method with the waterfall method and the rule base method for parsing the dictionary data. Based on the results of the analysis and design of the Aceh language translator application, it can be seen that; The design of an Acehnese translator application can provide convenience in carrying out the process of translating Acehnese into Indonesia and vice versa, and the rule-based method is used to anticipate the limited number of words contained in the database, which are Indonesian words that have similarities in Acehnese made in a certain pattern of rules. The rule-based used in this application is the change rule in the front syllable, back syllable, middle syllable, and their combinations.